Clinical profile of acute on chronic liver failure patients in a tertiary care hospital: a cross-sectional study - Arun, C. S.; Kumar, Kandasamy A.; Rejoice, Poppy; Shafique, A.; Geetha, G. (International Journal of Advances in Medicine, 2025)
Background: Acute-on-chronic liver failure (ACLF) is characterized by the sudden worsening of chronic liver disease (CLD) and high short-term mortality. This study evaluated the clinical profiles, outcomes, and predictors of early mortality. Methods: A cross-sectional study was conducted in 51 patients with ACLF at Tirunelveli Medical College Hospital from April 2023 to April 2024. Clinical features, aetiologies, triggering factors, and prognostic scores such as model for end-stage liver disease (MELD), MELD-Na, chronic liver failure - organ failure (CLIF-OF), chronic liver failure - consortium acute-on-chronic liver failure (CLIF-C ACLF), APASL ACLF Research Consortium (AARC) were recorded. Outcomes, including intensive care unit (ICU) admission, readmission, early mortality, and transplant-free survival (TFS), were analyzed. Results: Ethanol-related CLD was most common in males 43 (84.3%), and CAM-related factors were the leading trigger 26 (51%). The clinical features included jaundice (100%), ascites (98%), and encephalopathy (56.9%). Early mortality occurred in 13 (25.5%), overall mortality in 15 (29.4%), ICU admission in 40 (78.4%), and readmission in 22 (43.1%). TFS was 72.5% at 28 days, 66.6% at 3 months, 58.8% at 6 months, and 52.9% at 1 year. Non-survivors had significantly higher MELD-Na (31.5±3.6 versus 27.9±3.6; p=0.0028), AARC (11.2±1.9 versus 8.1±1.3; p<0.0001), CLIF-OF (11.2±1.0 versus 8.9±1.1; p<0.0001), and CLIF-C ACLF scores (52.4±5.5 versus 42.4±5.1; p<0.0001). Among 5 cases receiving PLEX, early mortality was 20% versus 26.1% without plasma exchange (PLEX) (p=1.000), and 28-day TFS was 100% versus 69.6% (p=0.300). Higher MELD-Na and AARC scores were associated with increased risk of death (p=0.011 and p=0.033, respectively). Conclusion: Ethanol-related CLD was the predominant cause of ACLF, with complementary and alternative medicine (CAM)-related triggers. Higher MELD, MELD-Na, CLIF-OF, CLIF-C ACLF, and AARC scores predicted early death.